2020
DOI: 10.1161/circresaha.119.315215
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal RNA-Seq Analysis of the Repeatability of Gene Expression and Splicing in Human Platelets Identifies a Platelet SELP Splice QTL

Abstract: Rationale: Longitudinal studies are required to distinguish within versus between-individual variation and repeatability of gene expression. They are uniquely positioned to decipher genetic signal from environmental noise, with potential application to gene variant and expression studies. However, longitudinal analyses of gene expression in healthy individuals—especially with regards to alternative splicing—are lacking for most primary cell types, including platelets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 62 publications
0
51
0
Order By: Relevance
“…Leukocyte-depleted platelets were isolated as previously described from whole blood drawn from SARS-CoV-2–infected patients and healthy donors. 12 , 21 - 24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukocyte-depleted platelets were isolated as previously described from whole blood drawn from SARS-CoV-2–infected patients and healthy donors. 12 , 21 - 24 …”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq and analysis were performed on total RNA extracted from platelets isolated from SARS-CoV-2–infected patients and age- and sex-matched healthy donors, as before. 12 , 21 - 24 RNA-seq files were deposited in NCBI short-read archives under PRJNA634489.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that platelet gene expression levels are highly correlated within an individual between Visits 1 and Visit 4. [23] Therefore in all subsequent analyses, these two visits were treated equivalently as no-drug treatment visits and no adjustment for leukocyte contamination was performed.…”
Section: Aspirin's Effects Of Platelet Gene Expressionmentioning
confidence: 99%
“…While the platelet transcriptome is dynamically altered in disease states (Best et al, 2018;Wurdinger et al, 2020), in the absence of disease platelet gene expression remains remarkably stable (Rondina et al, 2020). One of the challenges in using TEPs as liquid biopsy for cancer diagnostics is to understand which transcriptomic profiles are specifically associated with, for example, inflammation, other non-cancerous processes, and therapeutics (anti-coagulants and other pharmacological treatments).…”
Section: : Translation Of Tep Biomarkers Into the Clinicmentioning
confidence: 99%